The evolutionary history of aphids and a hypothesis on the coevolution of aphids and plants (Bollettino di zoologia agraria e bachicoltura, 2024)
Fossil aphids, including several specimens recently found in amber from the Cretaceous and the Lower Tertiary, not yet described, and comparison between the aphid fauna of the past and the recent fauna, indicate two major faunal changes, which are confirmed by the new findings. The first change happened at or dose to the Cretaceous-Tertiary boundary, 50-70 million years ago. The composition of the faunas, respectively about 75-80 million years old and about 35-45 million years old, are described and compared. Most aphid families present in the Cretaceous became extinct before the Lower Tertiary, the period in which the Baltic amber was produced. In the Lower Tertiary most recent families were present, but the families Aphididae and Lachnidae were much less rich in species than they are today, so the second change happened after the Oligocene. These changes are described as consequences of changes ofthe dominant flora elements, I) from gymnosperms to angiosperms at the K-T-boundary, and 2) from predominantly woody angiosperms to herbs in the middle of the Tertiary, especially herbs belonging to the plant families Poaceae and Asteraceae, which became rich in species during the Upper Tertiary and now contain the hosts of most aphids. Among new species of Cretaceous age are representatives of the families Canadaphididaeand Palaeoaphididae, previously' only known from Canadian amber deposited in a secondary site and from the former USSR. Two additional specimens of Canadaphis carpenteri Essig, 1938, show a long rostrum, not visible in the holotype. The presence of siphuncular pores shows that Canadaphidoidea is a synonym of Aphidoidea. Also a representative ofTajmyraphididae, previously only known from Russia with a long rostrum and bilobed posterior end of the abdomen has been found in the Cretaceous Canadian amber. Instead of siphuncular pores it carries small cuticular fields with very small pale spots.
Keywords: Aphidina; coevolution; host plants; fossil aphids